Diagnostic study of the maize-based system in South and East Africa: pathways to sustainable intensification and diversification - a case study of Nakuru and Makueni counties in Kenya - Kanda, E. (International Water Management Institute (IWMI), 2024)
In Kenya, agriculture is mostly rainfed despite about 85% of the country being arid and semi-arid. The poor spatial and temporal distribution of rainfall makes rainfed agriculture a risky venture and makes the country susceptible to climate change and variability induced shocks. Furthermore, Kenya’s reliance on rainfed maize production in meeting its food needs and growing consolidation of production toward maize and dry beans has rendered the country increasingly vulnerable to supply disruptions and food shortages. Expansion of crop production to marginal lands that receive lower than normal rainfall requires investment in irrigation technologies. However, blanket one-size fits all technologies are not sustainable and therefore there is a need to design appropriate and fit-for purpose interventions in irrigated agriculture. This study aimed understanding the sustainability of the maize-based rainfed and irrigation system and identifying areas of intervention in the context of the key problems, opportunities, and farmers' preference. The counties considered were two contrasting agro-ecological zones i.e. Nakuru County (humid) and Makueni (Semi-arid) in order to obtain representative findings on agricultural production and range of interventions. Five out of six sub-counties were selected in Makueni County. In Nakuru, 23 wards out of 55 were eligible (based on irrigation suitability mapping and salinity levels) for selection and 8 wards were finally selected which covered 8 out of 11 sub-counties. 161 and 150 households in Makueni and Nakuru respectively were randomly selected for the study. Questionnaires were and Key informant interviews were adopted in the study. The findings indicated that most of the farmers use traditional irrigation methods (furrow, flood and basin) with only 38% and 23% in Nakuru and Makueni respectively using sprinkler and drip systems. Food security was ranked as the main driver for irrigation practise in the two counties. Most respondents (80%) were dissatisfied with their land productivity under a rainfed system in Makueni, while most (53%) were satisfied in Nakuru County. Although rainfed farmers are interested in starting irrigation, water scarcity is a limiting factor. Lack of extension services and training is another factor hindering irrigation practise. The assessment of the benefit-cost ratio (BCR) of the major crops indicated that only tomatoes in Makueni County are profitable in irrigated conditions. Kales (under irrigation) and beans (under rainfed) were profitable in Nakuru. The low profitability of major crops includes high input costs and low yields. Profit margins drive agribusiness and therefore sustainability of farming systems. Maize farming was not profitable in the two counties though the BCR value is closer to 1.0 in Nakuru implying that minimal interventions can be introduced to enhance profitability of maize farming in Nakuru. These interventions can include subsidies on farm inputs, and extension support and training. Profitability of farming enterprises in Makueni seems to favour high-value crops (vegetables) under irrigated conditions. Diversification of food systems is important practise for sustainable agricultural production. Sustainable diversification and intensification is determined by diversity of farm characteristics such as farm size and land tenure. Most farmers in both Makueni and Nakuru own less than 5 ha of land. This affects the selection of crops to be grown. Farmers who own large tracts of land (>10 ha) prefer maize or other cereals to vegetables and vice versa. Most farmers have private land ownership and thus secure land tenure although some farmers are in communal land, especially in Makueni County. Most farmers in the two counties practise crop rotation and intercropping as climate change adaptation strategies. Adoption of AU-IDAWM pathways 1 (Improved water control and watershed management in rain-fed farming, and pathway 2 is to better understand the informal FLID systems (farmer-led irrigation development (FLID) and contextually support and expand the sector are two important aspects that need to be adopted in the two counties to realize sustainable agricultural water management.